Recent Developments in the Chemistry of Pn(I) (Pn=N, P, As, Sb, Bi) Cations. Issue 1 (2nd December 2021) - Deb, Rahul; Balakrishna, P.; Majumdar, Moumita
Abstract: The Group 15 Pn(I) cations (Pn=N, P, As, Sb and Bi), which are isoelectronic with the donor‐stabilized carbones, have emerged recently. Despite the presence of two lone pair of electrons, the Pn(I) cations are weakly nucleophilic due to their inherent positive charge. Strongly electron‐donating supporting ligands including zwitterionic forms have been used to enhance their Lewis basicity. Furthermore, the chelating effect of cyclic ligand systems proved effective in increasing their nucleophilicity. The strategies involved in successfully isolating the fleeting Sb(I) and Bi(I) cations as the recent most achievements in this field have been discussed. The syntheses, structure, bonding situations and reactivity of the Pn(I) cations are discussed. An outlook on the periodic trends and future applications of these electronically unique electron‐rich cationic moieties have been provided. Abstract : The chemistry of Pn(I) cations, isoelectronic to donor‐stabilized carbones is an emerging field in contemporary main group research. Strategic syntheses of Pn(I) cations involving strong σ‐donor supporting ligands combined with their chelating effects have proven useful in enhancing the nucleophilicity despite inherent positive charge. Their unique bonding situations show potential applications in small molecule activation and catalysis.